The Comparison of Mushroom Substrate from Para Rubber vs. Cashew Sawdust on Growth and Yields of Pleurotus Ostreatus - Sour, Vannak Sour; Piseth Sour; Young Vorn; Dina Noun (International Journal of Sustainable Applied Sciences, 2024)
In Cambodia, para rubber sawdust is commonly used to cultivate oyster mushrooms due to its availability as a byproduct from wood factories, but country's significant cultivated cashew could be an alternative substrate. Hence, exploring new substrates becomes essential for farmers when there's a scarcity or price hike in para rubber. This study is in purpose of investigation the impact of para rubber vs. cashew sawdust and different mixture formulas on the growths and yields of Pleurotus ostreatus. The experiment was conduct in Factorial in CRD with two main factors: A) two different saw dusts which were para rubber sawdust and cashew sawdust and factor (B) was mushroom mixture formulas (B1 – B6). B4 of cashew sawdust displayed the highest efficiency at 32.24%, while B3 and B4 of para rubber sawdust showed efficiencies of 23.57% and 23.54%, respectively. In conclusion, based on this experiment, cashew proves more effective than para rubber for Pleurotus ostreatus production. Specifically, B4, consisting of 100kg of cashew sawdust, 8kg of rice bran, 1kg of calcium carbonate, 1kg of palm sugar, 1kg of sticky rice flour, and 0.2kg of magnesium sulfate, maximizes yields for P. ostreatus cultivation.